Erythropoietin couples hematopoiesis with bone formation. - Yusuke Shiozawa; Younghun Jung; Anne M Ziegler; Elisabeth A Pedersen; Jianhua Wang; Zhuo Wang; Junhui Song; Jingcheng Wang; Clara H Lee; Sudha Sud; Kenneth J Pienta; Paul H Krebsbach; et al. (PLoS ONE)
Background It is well established that bleeding activates the hematopoietic system to regenerate the loss of mature blood elements. We have shown that hematopoietic stem cells (HSCs) isolated from animals challenged with an acute bleed regulate osteoblast differentiation from marrow stromal cells. This suggests that HSCs participate in bone formation where the molecular basis for this activity is the production of BMP2 and BMP6 by HSCs. Yet, what stimulates HSCs to produce BMPs is unclear. Methodology/principal findings In this study, we demonstrate that erythropoietin (Epo) activates Jak-Stat signaling pathways in HSCs which leads to the production of BMPs. Critically, Epo also directly activates mesenchymal cells to form osteoblasts in vitro, which in vivo leads to bone formation. Importantly, Epo first activates osteoclastogenesis which is later followed by osteoblastogenesis that is induced by either Epo directly or the expression of BMPs by HSCs to form bone. Conclusions/significance These data for the first time demonstrate that Epo regulates the formation of bone by both direct and indirect pathways, and further demonstrates the exquisite coupling between hematopoiesis and osteopoiesis in the marrow.